2019
DOI: 10.1515/eces-2019-0027
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Packaging Systems on Selected Antioxidant Properties of Frozen-Stored Broccoli

Abstract: Broccoli has a very good nutritive value, high antioxidant activity and pro-healthy potential. Freezing is one of best methods for vegetable storage and broccoli belongs to the group of vegetables subjected to this process on an industrial scale. This work investigates the effect of type of container: low density polyethylene (PE-LD) bags and oriented polystyrene (OPS) boxes on selected quality parameters in frozen broccoli. The experimental material was the broccoli cultivar LordF1. The vegetable was subjecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…In particular, Gebczyński and Lisiewska [113], and Gebczyński and Kmiecik [112] highlighted a negative effect of frozen storage on the AOA of both broccoli and cauliflower prepared for consumption mostly related to the parallel reduction of vitamin C and polyphenols, while β-carotene and carotenoids variations were very limited and/or statistically significant only after 12 months of storage. On the contrary, Hunter and Fletcher [102], on peas and spinach after the decrease of AOA due to blanching and freezing, did not observe further significant losses during storage at −20 • C. This effect was also observed by Korus and Lisiewska [98] on kale leaves stored for 12 months, despite the decrease of vitamin C and polyphenols, as well as by Kapusta-Duch et al [109] in cauliflower stored at −22 • C for up to 3 months. Murcia, Jiménez and Martínez-Tomé [114], who evaluated the loss of AOA due to frozen storage (−20 • C for 8 months) on thirteen types of vegetables, evidenced different effects depending on both the vegetable and the method of analysis applied for the AOA determination.…”
Section: Effect Of Frozen Storage and Storage Temperaturementioning
confidence: 68%
See 1 more Smart Citation
“…In particular, Gebczyński and Lisiewska [113], and Gebczyński and Kmiecik [112] highlighted a negative effect of frozen storage on the AOA of both broccoli and cauliflower prepared for consumption mostly related to the parallel reduction of vitamin C and polyphenols, while β-carotene and carotenoids variations were very limited and/or statistically significant only after 12 months of storage. On the contrary, Hunter and Fletcher [102], on peas and spinach after the decrease of AOA due to blanching and freezing, did not observe further significant losses during storage at −20 • C. This effect was also observed by Korus and Lisiewska [98] on kale leaves stored for 12 months, despite the decrease of vitamin C and polyphenols, as well as by Kapusta-Duch et al [109] in cauliflower stored at −22 • C for up to 3 months. Murcia, Jiménez and Martínez-Tomé [114], who evaluated the loss of AOA due to frozen storage (−20 • C for 8 months) on thirteen types of vegetables, evidenced different effects depending on both the vegetable and the method of analysis applied for the AOA determination.…”
Section: Effect Of Frozen Storage and Storage Temperaturementioning
confidence: 68%
“…When the effect of freezing has been evaluated by analyzing the antioxidant capacity data of blanched vegetables before and after the freezing process, no variation in the AOA was found in green and white cauliflower, kale leaves and broccoli florets [98,[108][109][110]. These results highlight that if frozen foods are handled and processed properly, their functional properties can be retained during freezing.…”
Section: Effect Of Freezing and Freezing Temperaturementioning
confidence: 90%
“…Controlled atmosphere storage and modified atmosphere packaging are also a practical alternative for preserving Brassica vegetables' quality and marketability during a longer shelf-life ( 44 , 191 ) with respect to ordinary canning leading to considerable loss of GLs following their thermal degradation ( 44 ). It has been reported that polyethylene-, polypropylene-, and polystyrene-MAP better preserved aliphatic, indole, and aromatic GLs as well as the nutritional quality of broccoli florets of various cultivars (Parthenon, Aishwarya, and Lord F1) stored until 3 weeks, even at relatively higher temperatures ( 144 , 175 177 ). Similarly, acceptable sensory quality texture and antioxidant composition of broccoli florets was maintained up to 25 days' storage after using an innovative MAP made of gas promoter-gas barrier blending materials, maintaining an internal atmosphere of 8.2% CO 2 and 2.0% O 2 ( 178 ).…”
Section: Factors Affecting Gls Synthesis and Accumulationmentioning
confidence: 99%